Room Freshener From a Mixture of Orange Peel, Clove and Cinnamon CloZinPeel(Clove + Cinnamon + Peel) - Samudra Iswahyudi; Argyant Luven Nurtaufik; Thio Juan Raehan Abdellah; Muhammad Bachrul Alam; Bintang Sandriesta Putera; Andri Syarif Hidayat; Vany Destiany (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
This study aims to develop an eco-friendly room freshener using sweet orange peel (Citrus sinensis), clove (Syzygium aromaticum), and cinnamon (Cinnamomum verum) in the form of a reed diffuser. Synthetic fresheners are often perceived as unpleasant due to their strong aroma, while natural alternatives provide a softer and more relaxing fragrance. Orange peel, typically considered waste, contains bioactive compounds such as limonene and citral, which act as natural fragrance agents. Combined with the eugenol in clove and cinnamaldehyde in cinnamon, these natural ingredients offer antimicrobial and aromatic benefits. Extraction was performed using Soxhlet equipment and DOWANOL as solvent. The product was evaluated through organoleptic testing involving 25 respondents. Results showed that 52% of participants “liked” the product, 16% “strongly liked” it, while only 12% “disliked” it. These findings indicate that the formulation was well accepted and has potential as a sustainable product. The use of fruit peel waste as a fragrance ingredient not only supports waste reduction but also promotes the development of environmentally friendly consumer goods.